Pembelajaran Daring Melalui Game Edukasi Quizizz Terhadap Hasil Belajar Fisika - Nurfadilah Nurfadilah; Dian Pramana Putra; Riskawati Riskawati (Department of Physics Education, Universitas Mataram, 2021)
The type of research used in this research is Pre-Experimental Designs research. The objectives of this research are: 1) To describe the learning outcomes of students in class X MIPA at SMA Negeri 5 Bone before and after the implementation of online learning with the educational game Quizizz in learning; 2) Describe the improvement in learning outcomes of students in class X MIPA at SMA Negeri 5 Bone before and after the implementation of online learning using the Quizizz educational game in learning. The samples in this study were students of class X MIPA 1 SMA Negeri 5 Bone which consisted of 31 students. The data collection technique used in collecting data in this study was by means of a test consisting of a pretest and posttest in the form of multiple choices. The results of the descriptive analysis in this study showed that the scores obtained by students in the posttest were much higher than the scores obtained in the pretest. Where the average score in the pretest is 13.42 with a standard deviation of 4.20, while in the posttest the average score obtained by students is 23.98 with a standard deviation of 4.70. So there is an increase in student learning outcomes before and after being taught by applying the Quizizz educational game, where the increase is in the moderate category.